2018
DOI: 10.1016/j.psychres.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Details of attention and learning change in first-episode schizophrenia

Abstract: Impaired attention and learning functions are common in schizophrenia. The details of this impairment, and how these change across time, are not well known. We aimed to compare the parameters of well-known attention and learning neuropsychological tests in first-episode schizophrenia (FES) patients and healthy controls in a 2-year follow-up period. The performance of 28-25 FES patients and pairwise matched healthy controls on the Continuous Performance Test-Identical Pairs, the revised Hopkins Verbal Learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…In the present study, the dn-FES group showed severe and widespread cognitive deficits in all domains, and this observation was consistent with the previous studies that used the same instrument [5,35,36]. Schizophrenia has distinct cognitive impairments, including speed of processing [37], working memory [38], verbal learning [39], reasoning/problem solving [40], visual learning [41], attention/vigilance [42], and social cognition [43]. Our results showed that cognitive deficits were present at the onset of schizophrenia without considering the several factors, such as long-term antipsychotic treatment and prolonged illness course.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the dn-FES group showed severe and widespread cognitive deficits in all domains, and this observation was consistent with the previous studies that used the same instrument [5,35,36]. Schizophrenia has distinct cognitive impairments, including speed of processing [37], working memory [38], verbal learning [39], reasoning/problem solving [40], visual learning [41], attention/vigilance [42], and social cognition [43]. Our results showed that cognitive deficits were present at the onset of schizophrenia without considering the several factors, such as long-term antipsychotic treatment and prolonged illness course.…”
Section: Discussionsupporting
confidence: 92%
“…We found that SZ patients showed cognitive impairments in all domains, which is consistent with previous studies that used the same cognitive measurement [15]. Deficits processing speed [33], working memory [34], verbal learning [7], reasoning/problem-solving [35], visual learning [36], and attention/vigilance [37] were found in SZ patients. Similar cognitive impairments were also reported in studies investigating patients with other psychiatric diagnoses [3841]; however, the cognitive deficits were not as severe or as widespread as those seen in SZ patients.…”
Section: Discussionsupporting
confidence: 88%
“…P atients with schizophrenia display impairments in the processing of auditory sensory information, [1][2][3][4] including auditory event-related potentials (eg, mismatch negativity) 1,2,5,6 that are generated in layer 3 of the primary auditory cortex (A1). [7][8][9] Many individuals with schizophrenia also have deficits in auditory learning, 10 limiting their functional recovery during targeted sensory and cognitive training. 11 In A1, as in other cortical regions, learning requires the formation and stabilization of new dendritic spines, [12][13][14] and decreased density of layer 3 dendritic spines has been reproducibly observed in multiple brain regions in patients with schizophrenia, including A1.…”
mentioning
confidence: 99%